2015
DOI: 10.1080/09500693.2015.1042940
|View full text |Cite
|
Sign up to set email alerts
|

Performing a Choice-Narrative: A qualitative study of the patterns in STEM students’ higher education choices

Abstract: Students' science choices have long attracted attention in both public and research. Recently there has been a call for qualitative studies to explore how choices create a sense of fit for individual students. Therefore, this paper aims to study how science students' choices of higher education are performed and to uncover the patterns of students' construction of their choice-narratives. The paper is based on a qualitative study among 38 Danish upper secondary school students. The theoretical framework is nar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 37 publications
(40 reference statements)
0
33
0
2
Order By: Relevance
“…Interests are directive for the liking of related subjects and activities and the wish to spend more time and effort on these. Therefore, it is not surprising that interest is one of the most important factors in educational choices of students, including the choice for a higher educational programme (Eccles & Wigfield, 2002;Harackiewicz et al, 2008;Holmegaard, 2015).…”
Section: The Role Of Interests In the Higher Educational Choicementioning
confidence: 99%
See 3 more Smart Citations
“…Interests are directive for the liking of related subjects and activities and the wish to spend more time and effort on these. Therefore, it is not surprising that interest is one of the most important factors in educational choices of students, including the choice for a higher educational programme (Eccles & Wigfield, 2002;Harackiewicz et al, 2008;Holmegaard, 2015).…”
Section: The Role Of Interests In the Higher Educational Choicementioning
confidence: 99%
“…These quantitative studies show interest is mentioned more frequently than other factors and interests score highest on relative importance. Qualitative studies mainly show students balance their interests and future career possibilities, but often the students' interests are decisive for which programme they choose to enrol in (Archer et al, 2010;Holmegaard, 2015;Holmegaard et al, 2014).…”
Section: The Role Of Interests In the Higher Educational Choicementioning
confidence: 99%
See 2 more Smart Citations
“…Recent research has shown that students' STEM choices should be understood as a process rather than as a single decision (Holmegaard, 2015;Holmegaard, Ulriksen, & Madsen, 2012). However, when students have decided to enter higher education their choice process continues.…”
Section: The Expectancy-value Modelmentioning
confidence: 99%